FROM DIAGNOSIS TO RECOVERY: A CASE REPORT OF AN INFECTED URACHAL CYST IN AN ELDERLY MALE - Jadhav, Kavita; Venkatesh, Gadi; Waghmare, Rukmini; Akotkar, Shubham; Ahmad, Fahd; Waghmare, Yashashri (Indonesian Journal of Urology, 2025)
Objective: This case report was aimed to present an infected urachal cysts in an elderly male. Case(s) Presentation: We are presenting a case of an infected urachal cyst actively draining pus through the umbilicus in a 72-year-old male. He was managed by surgical excision of that urachal cyst completely along with omphalectomy after initial intravenous antibiotics and investigations. Discussion: In this instance, the patient complained of suprapubic discomfort, exudation of pus from the umbilical cord, and fever. Due to the variety of manifestations, the urachal cyst can frequently be interpreted as Meckel diverticulitis, pelvic inflammatory disorder, appendicitis, or infection of the urinary system. The probability of cancer ought to be weighed up while addressing an elderly with a urachal cyst. Urachal malignant tumor, which develops from the remaining epithelia of the urachal abnormalities, has an awful prognosis. The most typical presentation is hematuria. Conclusion: This case emphasizes the need for the inclusion of urachal anomalies in the differential diagnosis of abdominal discomfort with umbilical discharge even in the elderly patients. Keywords: Urachal cyst, elderly male, excision.